Resolução de problemas com construções geométricas: uma análise das questões de geometria nos exames ENQ e ENA - COELHO, Denison Moreno (2019)
This work aims to present a study on the resolutions involving geometric constructions based on the studies carried out in the MA-13 PROFMAT discipline and from reputable authors who researched on the subject. A brief study will be presented on the history of geometry from ancient Egypt to the present day and the history of geometric design in teaching. Soon after will be seen some basic constructions and their applications in the ENQ and ENA exam. A quantitative content analysis will be performed on the issues involving geometric constructions in their resolutions in the ENA and ENQ exams over the past 3 years, serving as a basis for assessing the national use of these creative responses, in order to relate concepts and applications to your due visualization.